Endogenous benchmarks - David Hunter; Eugene Kandel; Shmuel Kandel; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2009)
This paper develops a new approach that controls for commonalities in actively managed investment fund returns when measuring their performance. It is well-known that many investment funds may systematically load on common priced factors omitted from popular models, exhibit similarities in their choices of specific stocks and industries, or vary their risk-loadings in a similar way over time. We propose a parsimonious model that uses the return on the group of mutual funds as a benchmark for each individual fund within that group. We demonstrate that this model substantially reduces the correlation between fund residuals from standard models used for equity and fixed-income funds, and improves the estimates of fund α's and β's from commonly used equity and fixed-income models.
Keywords: 330; Investmentfonds; Wertpapieranalyse; Kapitalertrag; Risiko; Beta-Faktor; Korrelation; Schätzung; USA